Analisis Faktor-Faktor yang Mempengaruhi Loyalitas Nasabah KSPPS BMT Maunah Cabang Desa Wangandawa Kabupaten Tegal - Liris Kristina; Elsha Novia Rachma Yuliari (Indo Publishing, 2025)
Customer loyalty is a key indicator of the long-term success of an Islamic financial institution. KSPPS BMT Maunah shows a high level of customer loyalty, but there is no empirical data explaining the factors that influence it. This study aims to examine the influence of service quality, corporate image, and trust on customer loyalty. The population in this study were all customers of KSPPS BMT Maunah Wangandawa Village Branch. The sampling technique used the saturated method, namely the entire population was sampled with 153 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that partially, the variables of service quality and corporate image did not significantly influence customer loyalty. Meanwhile, trust had a positive and significant influence on customer loyalty. Simultaneously, service quality, corporate image, and trust had a significant influence on customer loyalty. These findings indicate that trust is a dominant factor in shaping customer loyalty at KSPPS BMT Maunah.